The Effect of Employee Engagement, Work Environment, and Organizational Learning on Organizational Commitment at the Nimco Indonesia - Khalis, Fajar; Ariani, Dorothea Wahyu (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the effect of Employee Engagement, Work Environment, and Organizational Learning on Organizational Commitment at the Nimco Indonesia. The sample consisted of 83 employees with primary data collected through Google Form questionnaires. This study adopterd a quantitativer rerserarch merthod with ther aim of erxploring spercific rerlationships bertwerern variablers at Nimco Indonersia heradquarterrs. Data analysis was carried out with a Likert scale and statistical tests using SPSS. The results showed a positive and significant effect of Employee Engagement and Work Environment on Organizational Commitment, while Organizational Learning had no significant effect. The implications of the results of this study can help companies in increasing employee organizational commitment.